A Case with Familial Mediterranean Fever which Responds Well to Adalimumab Treatment - Özgür ORTANCIL; Aslan SANLI; Perihan SAPMAZ BULMUŞ; Selda SARIKAYA (Archives of Rheumatology, 2011)
Ankylosing spondylitis (AS) may accompany Familial Mediterranean fever (FMF). In this article, we present a 48-year-old male FMF case with accompanying AS who was successfully treated with a tumor necrosis factoralpha (TNF-α) inhibitor (adalimumab). Colchicine and other disease modifying antirheumatic drug (sulfasalazine and leflunomide) treatments had been given before the initiation of the TNF-α inhibitor, but FMF attacks could not be adequately controlled by these treatments. When adalimumab was coadministered with colchicine, the disease activity of AS was improved and the frequency and the severity of the FMF attacks were reduced during the one-year follow-up. We conclude that TNF-α blockers may be a therapeutic option when conventional treatment is ineffective in patients with FMF.